Interrogating the precancerous evolution of pathway dysfunction in lung squamous cell carcinoma using XTABLE - Roberts, Matthew; Ogden, Julia; Hossain, AS Mukarram; Chaturvedi, Anshuman; Kerr, Alastair RW; Dive, Caroline; Beane, Jennifer Ellen; Lopez-Garcia, Carlos (eLife, 2023)
Lung squamous cell carcinoma (LUSC) is a type of lung cancer with a dismal prognosis that lacks adequate therapies and actionable targets. This disease is characterized by a sequence of low- and high-grade preinvasive stages with increasing probability of malignant progression. Increasing our knowledge about the biology of these premalignant lesions (PMLs) is necessary to design new methods of early detection and prevention, and to identify the molecular processes that are key for malignant progression. To facilitate this research, we have designed XTABLE (Exploring Transcriptomes of Bronchial Lesions), an open-source application that integrates the most extensive transcriptomic databases of PMLs published so far. With this tool, users can stratify samples using multiple parameters and interrogate PML biology in multiple manners, such as two- and multiple-group comparisons, interrogation of genes of interests, and transcriptional signatures. Using XTABLE, we have carried out a comparative study of the potential role of chromosomal instability scores as biomarkers of PML progression and mapped the onset of the most relevant LUSC pathways to the sequence of LUSC developmental stages. XTABLE will critically facilitate new research for the identification of early detection biomarkers and acquire a better understanding of the LUSC precancerous stages.
Keywords: precancerous lesions; lung squamous cell carcinoma; transcriptomics; chromosomal instability; shiny app